GENESIS OF THE LEGAL BASIS OF LOCAL GOVERNMENT: CONTENT-ANALYSIS - Olshanskyi , O. (Theory and Practice of Public Administration, 2020)
Summarized the particular results of content analysis of the local government key legislative acts adopted during 1990-2001. Described the stages of its methodology: the web resource of the Verkhovna Rada of Ukraine was chosen as a source of information, the categorical network was formed from the text documents (legislative acts), contextual units defined as institutional and material-financial resource of local government: the concept of “local government”; system of local government; functions, competence, powers of local government bodies; financial and economic basis of local government. Presented a fragment of the content analysis matrix, its results are analyzed on the example of one contextual unit – the concept of “local government”.Defined the contradictory and incorrect provisions of certain legal acts, in particular: 1) regarding the administrative levels in the system of local government, although by the nature of local government its organizational structure should not have levels and managerial hierarchy; 2) the inconsistency of the local government territorial basis and the existing administrative-territorial structure of Ukraine, etc.Conducted a review of the latest law drafts on amendments to the Constitution of Ukraine on decentralization about such definitions as “local government” and “territorial community”. Revealed the contradictions of the definitions given in the law drafts to the requirements of the formal logic laws – the law of identity and the law of contradiction.Formulated the proposals to clarify the categories of “local government” and “territorial community” in the process of modernizing the legislation on the local government functioning in Ukraine, namely: local government is a state-guaranteed right and objective ability of local communities to address the local development issues; territorial community is a social community of residents of villages, settlements, cities or their unions in accordance with the law norms, united around the achievement of common goals of the collective life.